The Effect of Customer Relations and Marketing Communication on Competitive Advantage and Customer Loyalty - Taufik Zulfikar; Sucherly; Undang Juju (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Competitive advantage is achieved when a company runs a marketing strategy by producing products and services different from those of other competitors and/or producing cheaper products and services, which creates a superior value. Repeat purchase is a manifestation of customer satisfaction with the value received, and customer loyalty reflects companies with competitive advantages. This research aims to determine the impact of customer relations and marketing communication on competitive advantage, which affects customer loyalty. The research method used is a survey aimed at 400 hotel customers, and the analytical instrument used is the Structural Equation Model (SEM). The research shows that there is an influence of competitive advantage on customer loyalty, Customer relationship, and marketing communication, which affect competitive advantage both partially and simultaneously. Customer loyalty will happen when a company has a competitive advantage, encouraged by customer relationships and optimal marketing communication. This research highlights that loyalty is not merely the outcome of customer satisfaction but is rooted in a firm’s ability to build trustful relationships, communicate effectively, and sustain competitive advantage.